Fungsi Akuntansi Syariah pada BMT-BMT di Tangerang Selatan - SRI INDARTI (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2017)
One of the important agenda of Muslims is the problem of poverty alleviation. One of the Islamic financial institutions present the most strategic and functional to alleviate poverty ummah is BMT (Baitul Mal wat Tanwil). Accounting as one of the tools that are necessary in a financial institution is functionally a means of accountability and resources must be based on sharia. This study was done in order to determine how the characteristics and accounting functions of sharia in the BMT-BMT in South Tangerang, this study included 37 respondents (managers, administrators, supervisors) of 17 BMT in Tangerang south. The results of this study indicate BMT is growing rapidly in South Tangerang in the last five years and it is known that Islamic accounting functions in BMT in South Tangerang is the first, the accounting function as a form of sharia, both vertical and horizzontal, both accounting functions of sharia as a source of information for decision-making related closely with the availability of Islamic financial reports and human resources.